Differences in physiological variables of U23 cyclists between normoxia and hypoxia - Glomser, G.; Leo, P. (Journal of Science and Cycling, 2022)
For elite cyclists, the effect of altitude on physiological parameters and thus on endurance performance involves a complex interplay of training, physiological adaptation, and recovery. Since the summer Olympic games 1968 in Mexico City extensive research was conducted to study the effects of altitude training on the human body, as the physiological response to the altitude stimulus can have a legal performance enhancing effect for altitude and sea level endurance performance.